JAK3 restrains inflammatory responses and protects against periodontal disease through Wnt3a signaling. Issue 7 (20th May 2020) - Lü, Lanhai; Yakoumatos, Lan; Ren, Junling; Duan, Xiaoxian; Zhou, Huaxin; Gu, Zhen; Mohammed, Muddasir; Uriarte, Silvia M.; Liang, Shuang; Scott, David A.; Lamont, Richard J.; Wang, Huizhi
Abstract: Homeostasis between pro‐ and anti‐ inflammatory responses induced by bacteria is critical for the maintenance of health. In the oral cavity, pro‐inflammatory mechanisms induced by pathogenic bacteria are well‐established; however, the anti‐inflammatory responses that act to restrain innate responses remain poorly characterized. Here, we demonstrate that infection with the periodontal pathogen Porphyromonas gingivalis enhances the activity of Janus kinase 3 (JAK3) in innate immune cells, and subsequently phospho‐inactivates Nedd4‐2, an ubiquitin E3 ligase. In turn, Wingless‐INT (Wnt) 3 (Wnt3) ubiquitination is decreased, while total protein levels are enhanced, leading to a reduction in pro‐inflammatory cytokine levels. In contrast, JAK3 or Wnt3a inhibition robustly enhances nuclear factor kappa‐light‐chain‐enhancer of activated B cells activity and the production of pro‐inflammatory cytokines in P. gingivalis ‐stimulated innate immune cells. Moreover, using gain‐ and loss‐of‐function approaches, we demonstrate that downstream molecules of Wnt3a signaling, including Dvl3 and β‐catenin, are responsible for the negative regulatory role of Wnt3a. In addition, using an in vivo P. gingivalis ‐mediated periodontal disease model, we show that JAK3 inhibition enhances infiltration of inflammatory cells, reduces expression of Wnt3a and Dvl3 in P. gingivalis ‐infected gingival tissues, and increases disease severity. Together, our results reveal a new anti‐inflammatory role for JAK3 in innate immune cells and show that the underlying signaling pathway involves Nedd4‐2‐mediated Wnt3a ubiquitination.